2020
DOI: 10.1590/1518-8345.3499.3282
|View full text |Cite
|
Sign up to set email alerts
|

Sensory and cognitive functions, gait ability and functionality of older adults

Abstract: Objective: to know the relationship between the sensory function, gait ability, and cognitive function with dependency in older adults. Method: a descriptive cross-sectional design, 146 older adults took part. Measurements: Snellen chart, Audiometer, Stereognosia tests, Semmes-Weinstein monofilament, basic aromas and flavors, GAITRite system, Montreal Cognitive Assessment Test, the Barthel Index, and the Lawton and Brody Index. Results: sensory function, cognitive function and gait explain 25% dependence on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…Such changes can limit the functionality of the elderly and increase their degree of dependence for carrying out daily activities. It is because sensory function and other factors explain 25% of the dependence of the elderly on basic activities and 21% of the instrumental activities of daily life (29) . Thus, it is crucial to pay greater attention to the sensory abilities of the elderly, especially those of the male gender since they showed worse QoL in this facet and differed statistically from the female gender in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Such changes can limit the functionality of the elderly and increase their degree of dependence for carrying out daily activities. It is because sensory function and other factors explain 25% of the dependence of the elderly on basic activities and 21% of the instrumental activities of daily life (29) . Thus, it is crucial to pay greater attention to the sensory abilities of the elderly, especially those of the male gender since they showed worse QoL in this facet and differed statistically from the female gender in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, time greater than or equal to 20 seconds in the TUG was associated with greater dependence on IADL (p=0.048), highlighting that the more complex activities, vital to have an independent routine in the community, may require better performance of the main functional systems. A Mexican cross-sectional study with 146 older people who used the Lawton and Brody Scale to assess IADL and the GAITRite system, a software connected to a portable walkway to assess mobility, showed that walking speed, cadence, and step length are variables that impact IADL ( 44 ) .…”
Section: Discussionmentioning
confidence: 99%
“…This facet, which assesses sensory functioning and the impact of sensory losses on QoL, had the highest mean score in the three groups at the two assessment points. The sensory organs allow older adults to perceive the different situations which surround them in the environment in which they live, contributing to their integration with the environment 29 . For the older women evaluated, these issues were not evaluated negatively, possibly because they were younger seniors, for whom such sensory losses may not be especially present in their daily lives.…”
Section: Discussionmentioning
confidence: 99%